Study of artificial production meat possibility in reared beluga (H. huso) with different diets - Mohseni, Mahmoud; Pourkazemi, M.; Fllahi, M.; Bahmani, M.; Sepahdari, A.; Pourali, H.R.; Seyad Hassani, M.H.; Kazemi, R.; Hallajiyan, A.; Salehi, M. (Iranian Fisheries Science Research Institute, 2016)
Four experiments were conducted to study of production meat in reared beluga (Huso huso) with different diets. In the first experiment, A 19-week feeding trial was conducted to evaluate dehulled soybean meal (DHSM) as a fish meal (FM) replacer in juvenile beluga, of initial body weight 8.25±0.08 g (mean±SD) in triplicate groups, fed six isoenergetic (20.1 mJ kg^-1) and isoproteic (45% crude protein) diets, resulting in 5%, 10%, 15%, 20% and 25% of fish meal protein being replaced by soybean protein. Growth performance was reduced significantly with the increasing of DHSM in the diets in the present study. In the next stage, triplicate groups of 315 fish averaging 300.25 ± 10.28 g (mean ± SD) were fed one of seven experimental diets for 14 weeks. Weight gain (WG), specific growth rate (SGR), feed effeciency (FE), protein efficiency of retio (PER) of fish fed 5%, 10% and 15% of soybean protein diets were significantly higher than those of fish fed 20%, 25% and 30% diets. Whole body protein, lipid, moisture content were unaffected among different treatments (P > 0.05). In the second experiment, A 2 × 4 factorial design was used to evaluate the dietary lysine and to determine the optimum dietary L-carnitine in sub-yearling beluga, reared in the indoor system. Twelve experimental diets were formulated and prepared to contain four lysine levels (0.75, 1.5, 2.25 and 4% diet) and two L-carnitine levels (300 and 600 mg/kg diet) at each lysine level. Fish averaging 23 ± 0.5 (mean±SD) were fed one of the experimental diets for 10 weeks. At the end of the experimental period, there were significant lysine and Lcarnitine effects (P <0.05) on growth performance and feed conversation ratio (FCR). These results may indicate that, weight gain (WG), FCR and protein efficiency ratio (PER) in fish fed diet containing 3% lysine and 600 mg L-carnitine/kg diet were significantly higher than those of fish fed control diet (P < 0.05). There were no significan dietary lysine and L-carnitine effects on glucose, cholesterol and ...